Santi Romano against the state?. Issue 2 (30th August 2018) - Vinx, Lars
ABSTRACT: This paper argues that Santi Romano's legal institutionalism is driven by implicit normative assumptions that stand in tension with Romano's commitments to legal positivism and legal pluralism. Romano's approach to the individuation of legal orders is indefensible on purely descriptive grounds, as it rests on a picture of good social order. That picture, in turn, gives more prominence to the state, as an institution of institutions, than one would expect in a thoroughly pluralist legal theory. Romano's reflections on the different ways in which institutions can become legally relevant to one another is nevertheless highly valuable. It provides the toolkit for developing a normatively attractive conception of the legal relations of the state to other institutional orders.